Newly isolated sporopollenin microcages fromCedrus libaniandPinus nigrafor controlled delivery of Oxaliplatin - Mujtaba, Muhammad; Yılmaz, Bahar Akyauz; Cansaran-Duman, Demet; Akyuz, Lalehan; Yangın, Sevcan; Kaya, Murat; Çeter, Talip; Khawar, Khalid Mahmood (Cold Spring Harbor Laboratory, 2020)
AbstractSporopollenin-mediated controlled drug delivery has been studied extensively owing to its physicochemical and biological charachteristics. In the present study, sporopollenin was successfully extracted from pollen grains ofC. libaniandP. nigrafollowed by the loading of a commonly known anticancer drug Oxaliplatin. Both the drug loading and physicochemical features were confirmed by using light microscopy, FT-IR, SEM and TGA. For the first time, real-time cell analyzer system, xCELLigence, was employed to record the Oxaliplatin-loaded and sporopollenin-mediated cell death (CaCo-2 and Vero cells) in real time. Both the assays confirmed the slow release of Oxaliplatin from sporopollenin for around 40–45 h. The expression of MYC andFOXO-3genes significantly increased in CaCo2 cell and decreased non-cancerous Vero cell confirming that sporopollenin-mediated controlled release of Oxaliplatin was promoting apoptosis cell death preventing the spread of its negative effects to nearby healthy cells. All the results suggested thatC. libaniandP. nigracould be suitable candidates for slow delivery of drugs.
Keywords: 3. Good health